Effect of Engagement With Digital Interventions on Mental Health Outcomes: A Systematic Review and Meta-Analysis - Gan, Daniel Z. Q.; McGillivray, Lauren; Han, Jin; Christensen, Helen; Torok, Michelle (Frontiers in Digital Health, 2021)
Digital mental health interventions (DMHIs) present a promising way to address gaps in mental health service provision. However, the relationship between user engagement and outcomes in the context of these interventions has not been established. This study addressed the current state of evidence on the relationship between engagement with DMHIs and mental health outcomes. MEDLINE, PsycINFO, and EmBASE databases were searched from inception to August 1, 2021. Original or secondary analyses of randomised controlled trials (RCTs) were included if they examined the relationship between DMHI engagement and post-intervention outcome(s). 35 studies were eligible for inclusion in the narrative review and 25 studies had sufficient data for meta-analysis. Random-effects meta-analyses indicated that greater engagement was significantly associated with post-intervention mental health improvements, regardless of whether this relationship was explored using correlational (r = .24, 95% CI [.17, .32], Z = 6.29, p < .001) or between-groups designs (Hedges’ g = .40, 95% CI [.097, .705], p = .010). This association was also consistent regardless of intervention type (unguided/guided), diagnostic status, or mental health condition targeted. This is the first review providing empirical evidence that engagement with DMHIs is associated with therapeutic gains. Implications and future directions are discussed.